2002
DOI: 10.1128/jvi.76.12.6016-6026.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Macaque Resistance to Mucosal Simian Immunodeficiency Virus Infection Is Associated with a Postentry Block in Viral Replication

Abstract: Elucidation of the host factors which influence susceptibility to human immunodeficiency virus or simian immunodeficiency virus (SIV) infection and disease progression has important؉ T cells. Identification of this host mechanism will help further elucidate the biochemistry of reverse transcription and may suggest therapeutic strategies. Determining the prevalence of this host resistance mechanism among macaques may lead to better design of SIV pathogenesis and vaccine studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…While it is possible that immunization with MVA Gag may have contributed to the resistance of 256.90 to SIV infection, this is also unlikely to be the sole explanation for this result, since such solid protection against challenge with pathogenic SIVmac strains is rarely, if ever, observed in animals immunized with recombinant poxviruses. Resistance to mucosal SIV infection among control animals has been observed in other vaccine studies and often complicates the interpretation of protection data obtained from mucosal challenges (29). Thus, some animals may have an inherent resistance to mucosal infection that is poorly understood at present (29).…”
Section: Fig 6 Siv Rna In Plasma and Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…While it is possible that immunization with MVA Gag may have contributed to the resistance of 256.90 to SIV infection, this is also unlikely to be the sole explanation for this result, since such solid protection against challenge with pathogenic SIVmac strains is rarely, if ever, observed in animals immunized with recombinant poxviruses. Resistance to mucosal SIV infection among control animals has been observed in other vaccine studies and often complicates the interpretation of protection data obtained from mucosal challenges (29). Thus, some animals may have an inherent resistance to mucosal infection that is poorly understood at present (29).…”
Section: Fig 6 Siv Rna In Plasma and Cd4mentioning
confidence: 99%
“…Resistance to mucosal SIV infection among control animals has been observed in other vaccine studies and often complicates the interpretation of protection data obtained from mucosal challenges (29). Thus, some animals may have an inherent resistance to mucosal infection that is poorly understood at present (29).…”
Section: Fig 6 Siv Rna In Plasma and Cd4mentioning
confidence: 99%
“…Some studies indicate that differences in host genetics or virus-specific immunity participate in virus control [1-3], but it is unlikely that a single factor is responsible.…”
Section: Introductionmentioning
confidence: 99%
“…As far as a genetic predisposition to control virus replication is concerned, we observed that the PBMC of monkey 954, when infected in vitro, were equally susceptible to virus infection as were the PBMC of other monkeys. Thus, any genetic restriction factor of virus replication at the level of virus entry or post-entry (Peng et al, 2002;Pal et al, 2002) was ruled out. Conversely, it is very likely that the limited infection observed in monkey 954 was due to the very low amount of virus taken up by the rectal mucosa, as a consequence of the incomplete delivery of virus inoculum.…”
Section: Discussionmentioning
confidence: 99%